Fundamentals of neural networks architectures, algorithms, and applications - Fausett, Laurene V. (Prentice Hall, 1994)
Providing detailed examples of simple applications, this new book introduces the use of neural networks. It covers simple neural nets for pattern classification; pattern association; neural networks based on competition; adaptive-resonance theory; and more. For professionals working with neural networks.